PENGARUH KELEMBAPAN RELATIF DAN SUHU TERHADAP AKTIVITAS GLUKOAMILASE ASPERGILLUS FLAVUS PADA PENYAKIT SIMPANAN GAPLEK - H. A. Oramahi, Christanti Sumardiyono, Nursamsi Pusposendjojo, dan Haryadi . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2009)
The effect of relative humidity and temperatur to glucoamylase activity of Aspergillus flavus on storage disease of dried cassava. Aspergillus flavus is the most important species because of its toxigenic caracteristic on agricultural product. Among several Aspergillus species growing on dried cassava. This study was conducted to show the role of glucoamylase produced by Aspergillus flavus fowards the storage disease of dried cassava. The effect of RH and storage room temperature to glucoamylase activity was evaluated for 4 months using Randomized Completely Block Design (Factorial). Variables observed were glucoamylase activity and starch content of dried cassava. Glucoamylase activity could be used as an early indicator of the infestation of dried cassava by Aspergillus while the change of dried cassava color had not been visible. Starch content of dried cassava decreased during the storage. Due to the glucoamylase activity of A. flavus which degrading starch into glucose. The interaction effect of RH and storage room temperature to glucoamylase activity of A. flavus was significant.